Reviving "Dead Letters": Reimagining Federal Rule of Evidence 410 as a Conditional Privilege - Cornick, Peter G (Vanderbilt law review, 2020)
Though understudied relative to its fellow specialized relevance rules, Federal Rule of Evidence 410 protects a crucial element of the criminal justice system: plea negotiations. As written, the rule prevents the admission of evidence gathered during plea discussions, which helps assure criminal defendants that their candid discussions with prosecutors will not harm them in any future proceeding. But the Supreme Court has greatly weakened Rule 410, permitting broad waiver of the rule's protections that run afoul of Congress's purpose in creating the rule and its plain language. In light of these developments, the Note argues that Rule 410 should be reconceptualized as a conditional privilege. Conditional privileges share many attributes with the more familiar absolute privileges, but conditional privileges often apply to communications with governmental entities and can be overcome by an ad hoc showing of necessity. This Note will elaborate on why and how Rule 410 should be reimagined as a conditional privilege and how this change will better effectuate Rule 410's original goals of promoting effective plea discussions.